VD_FINDINFO Décision / 2012 / 529 vom 4. Oktober 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)